Analisis Penerapan Islamic Good Corporate Governance (IGCG) pada Bank Pembiayaan Rakyat Syariah Hikmah Wakilah Banda Aceh - Abidin, Zainal (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
The Syari'ah Financial Institution has a very strategic role in the efforts of developing a people's economy because the Shari'ah bank is oriented to benefits not only on profit maximization. The formulation of the problem in this paper is: How is the concept and application of Islamic Good Corporate Governance (IGCG) in Islamic Financial Institutions; and How the implementation of Good Corporate Governance in BPRS Hikmah Wakilah Banda Aceh. The purpose of writing is: To find out the concepts and application of Islamic Good Corporate Governance (IGCG) in Islamic financial institutions and also analyze the implementation of the concept of Islamic Good Corporate Governance (IGCG) in BPRS Hikmah Wakilah Banda Aceh. This study uses qualitative research methods, the approach taken is descriptive, namely to know and describe the reality of the events studied or research conducted on independent or single variables. Islamic Good Corporate Governance (IGCG) in Islamic Financial Institutions is very different as applied in conventional financial institutions. Islamic financial institutions always pay attention to aspects of legal sources, namely the Qur'an and the hadith, the principle of adherence to Islamic law is used as a basis in bermuamalah which does not contain elements of maisir, usury and gharar in every transaction. Management of PT. BPRS Hikmah Wakilah is in line with its vision and mission of providing services to the community, namely the shuttle system. So that customers who are small and medium entrepreneurs do not have to leave their place of business to deposit payments to the BPRS. Application of Islamic Good Corperate Governance at PT. BPRS Hikmah of Wakilah, namely with a system of transparency, trustworthiness and a guarantee mechanism for sharia compliance, so that BPRS Hikmah of time gets the trust of the community and stakeholders.